2002
DOI: 10.14356/kona.2002027
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation Mechanism of Suspended Particles Using the Hydrophilic/Hydrophobic Transition of a Thermosensitive Polymerx [Translated]<sup>†</sup>

Abstract: We examined the f locculation of suspended particles using a thermosensitive polymer which undergoes a reversible hydrophilic/hydrophobic transition when heating or cooling its aqueous solution. As a thermosensitive polymer poly (N-isopropylacrylamide)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 3 publications
(6 reference statements)
3
25
0
Order By: Relevance
“…It is important to note that because the hydrophilic/hydrophobic transition of thermosensitive polymer is reversible, the flocs disorganize and return to the stable suspended particles upon cooling below the transition temperature of the polymer. The compaction mech- anism shown here was confirmed using poly(NIPAM) and kaolin suspension [2,3].…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…It is important to note that because the hydrophilic/hydrophobic transition of thermosensitive polymer is reversible, the flocs disorganize and return to the stable suspended particles upon cooling below the transition temperature of the polymer. The compaction mech- anism shown here was confirmed using poly(NIPAM) and kaolin suspension [2,3].…”
Section: Introductionsupporting
confidence: 65%
“…In an effort to alleviate this problem, the authors proposed a novel flocculation/compaction method using thermosensitive polymers [2,3]. Thermo-sensitive polymers are soluble in water at low temperature, but are insoluble above the intrinsic transition temperature of the polymer [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of PNIPAM to undergo controlled transitions from hydrophobic to highly hydrophilic has sparked considerable interest in its suitability as a surface modification reagent in minerals processing. A large number of studies have found PNIPAM to be a highly successful agent for facilitating mineral aggregation and consolidation [9][10][11][12][13][14][15], however questions remain regarding PNIPAM-induced aggregation mechanisms. In typical settling operations, flocculation occurs as a result of polymer bridging between mineral particles, which causes them to form aggregates [16].…”
Section: Introductionmentioning
confidence: 99%